(untitled) (International Journal of Engineering and Computer Science, 2018)
— Cloud computing refers to applications and services that run on a distributed network using virtualized resources and accessed by common Internet protocols and networking standards. Cloud computing takes the technology, services, and applications that are similar to those on the Internet and turns them into a self-service utility. Without adequate privacy protection, the system can be easily misused, e.g., to track users target them for home invasion. introduce LocX, a novel alternative that provides significantly-improved location privacy without adding uncertainty into query results or relying on strong assumptions about server security. Our key aim is to apply secure user-specific, distance-preserving coordinate transformations to all location data shared with the server. The friends of a user share this user’s secrets, so they can apply the same transformation to destination. This allows all location queries to be evaluated correctly by the server, but our privacy mechanisms guarantee that servers are unable to see or infer the actual location data from the transformed data or from the data access. show that LocX provides privacy even against a powerful adversary model, and we use prototype measurements to show that it provides privacy with very little performance overhead, making it suitable for today’s mobile devices.